2009
DOI: 10.1177/183335830903800105
|View full text |Cite
|
Sign up to set email alerts
|

The Risk and Consequences of Clinical Miscoding Due to Inadequate Medical Documentation: A Case Study of the Impact on Health Services Funding

Abstract: As coded clinical data are used in a variety of areas (e.g. health services funding, epidemiology, health sciences research), coding errors have the potential to produce far-reaching consequences. In this study the causes and consequences of miscoding were reviewed. In particular, the impact of miscoding due to inadequate medical documentation on hospital funding was examined. Appropriate reimbursement of hospital revenue in the casemix-based (output-based) funding system in the state of Victoria, Australia re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 32 publications
0
98
0
2
Order By: Relevance
“…In the present study the average number of reported comorbidities in patients was clearly higher for US patients, most likely due to the financial incentives associated with coding [16], which may result in PJI rates in the US being underestimated after adjustment for these reported comorbidities. However, reimbursement of health services in Australia also depends on clinical coding [17], but did not result in a higher number of reported comorbidities, so that it does not seem likely that this will explain the results entirely. Another issue is the ability to correctly identify PJI from administrative data.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study the average number of reported comorbidities in patients was clearly higher for US patients, most likely due to the financial incentives associated with coding [16], which may result in PJI rates in the US being underestimated after adjustment for these reported comorbidities. However, reimbursement of health services in Australia also depends on clinical coding [17], but did not result in a higher number of reported comorbidities, so that it does not seem likely that this will explain the results entirely. Another issue is the ability to correctly identify PJI from administrative data.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have observed that variations in diagnostic criteria can affect estimates of disease prevalence,2 and the complexities of clinical coding systems for electronic healthcare records can lead to inconsistent data recording 3. This will lead to uncertainties with respect to disease prevalence and mortality,4 impact on clinical care, have additional health service implications such as affecting funding5 and potentially influence identification of patients for clinical trials. Previous studies have compared general practice coding and disease prevalence with other unlinked data sources, including paper notes 6 7.…”
Section: Introductionmentioning
confidence: 99%
“…-clinical data, electronic health records and clinical coding ( [12,23,33,37,44,45,50,52,58]) and definition of data and information quality in eHealth ( [9,20,24,36,53]) -the impact of data quality and information processing on medical records ( [3,4,18,22,26,27,28,31,35,42,48,55,57]) -socio-technical aspects, including clinicians perspectives on EHRs and eHealth ( [13,17,41,55]) and patients' experiences and perspectives on eHealth and medical encounters with ICT ( [2,15,38]) -the study of quality of care, health outcomes and the studies of impact of ICT on health organisations ( [5,10,11,21,25,29,30,32])…”
Section: Overview Of Information Quality Assessment In Ehealthmentioning
confidence: 99%
“…Data stored in Electronic Health Records (EHRs) can be used for a wide range of purposes: patient care, administrative management, billing, services and resources management and planning, quality of care and financial audits, quality improvement programmes, as well as public health and medical research and reporting. Consequently, poor quality electronic health data can have a wide range of negative impacts, potentially affecting any of the following: standards of care, patient outcomes, audits, public health data and the current medical evidence [12].…”
mentioning
confidence: 99%